International Yearbook of Soil Law and Policy 2016 - Ginzky, Harald; Heuser, Irene L.; Qin, Tianbao; Ruppel, Oliver C.; Wegerdt, Patrick (International Yearbook of Soil Law and Policy, 2017)
IX, 430 p. 21 illus., 13 illus. in color.